2008
DOI: 10.2478/10004-1254-59-2008-1883
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Painters Exposed to Low Lead Levels

Abstract: Lead toxicity is a public health problem particularly to the children and to occupationally exposed adults. Evidence is mounting successively regarding the adverse health effects of lead at low levels. This study was undertaken to assess the antioxidant status of lead-exposed residential and commercial painters of Lucknow city in Uttar Pradesh, India. Thirty-five painters aged 20 to 50 years who had blood lead levels ≤400 µg L -1 were selected for the study from a population of 56 male painters initially scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
28
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 44 publications
12
28
1
Order By: Relevance
“…The treatment with bromelain did cause a significant reduction of Pb accumulation in the kidney and spleen, however, in the liver there was no detectable change observed due to bromelain treatment. The levels of serum MDA, a biomarker of metal-induced lipid peroxidation, were significantly increased in the groups exposed to both low and high doses of Pb in comparison to the control group which are consistent with the earlier studies [15,16]. Bromelain effectively reduced the MDA levels in the group exposed to a lower dose of lead.…”
Section: Discussionsupporting
confidence: 81%
“…The treatment with bromelain did cause a significant reduction of Pb accumulation in the kidney and spleen, however, in the liver there was no detectable change observed due to bromelain treatment. The levels of serum MDA, a biomarker of metal-induced lipid peroxidation, were significantly increased in the groups exposed to both low and high doses of Pb in comparison to the control group which are consistent with the earlier studies [15,16]. Bromelain effectively reduced the MDA levels in the group exposed to a lower dose of lead.…”
Section: Discussionsupporting
confidence: 81%
“…Generation of highly reactive oxygen species (ROS) aftermath of lead exposure may result in systematic mobilization and depletion of the cell intrinsic antioxidant defenses [Patra et al, 2011]. The results of this study support the hypothesis; since there was a signifi cant increase in the level of MDA and a signifi cant decrease in the endogenous antioxidants following intake of Pbacetate [Mohammad et al, 2008;Haleagrahara et al, 2011;Aziz, 2012]. This was explained by the high affi nity of lead for sulfhydryl (SH) group in several enzymes such as SOD, GSH and GPx; thus it can alter antioxidant activities by inhibiting functional SH groups in these enzymes as these enzymes are potential targets of lead toxicity [Marchlewicz et al, 2007].…”
Section: Discussionsupporting
confidence: 78%
“…The decrease in CAT activity might be due to the inhibition of haembiosynthesis of catalase by lead (Patil et al 2006). Mohammad et al (2008) have also reported that decrease in CAT activity was due to lead toxicity.…”
Section: Methodsmentioning
confidence: 96%